Novel high accuracy and coverage localization algorithm for wireless sensor networks - XIANG Man-tian1; SHI Hao-shan1; LI Li-hong2; LONG Cheng-zhi3 (Tongxin xuebao)
In order to achieve the geographic positions of random nodes in wireless sensor networks more efficiently and aiming at the defect that poor accuracy and coverage of traditional bounding box approach, a new localization algorithm was proposed based on concentric triple-hop of node communication range. The result of simulation and analysis shows that the proposed algorithm can optimize the constraints on nodes’ positions prominently, increase the estimation accu- racy and localization coverage significantly with sparse and non-uniform anchor distribution, decrease the energy con- sumption of sensor nodes accordingly.